Case Report: Hypercalcemic small-cell carcinoma of the ovary during pregnancy: diagnostic and therapeutic challenges - Tripepi, Marta; da Costa, Ana G.; Albergaria, Diogo; Costa, Andreia; Catarino, Ana; Duarte, Ana Luisa; Bartosch, Carla; Schuler, Veronica; Oliveira, Joana; Lima, Jorge; Casanova, João (Frontiers in Oncology, 2025)
Small-cell carcinoma of the ovary, hypercalcemic type (SCCOHT), is a rare, highly aggressive malignancy that predominantly affects young women. We report a 32-year-old pregnant woman diagnosed with SCCOHT during the first trimester of pregnancy. At 24 weeks, imaging revealed extensive peritoneal carcinomatosis. Following multidisciplinary evaluation, neoadjuvant chemotherapy was initiated, but the disease progressed. At 34 weeks, the patient underwent cesarean delivery followed by cytoreductive surgery. Despite achieving an initial complete resection, the disease recurred rapidly. The patient died shortly after completing adjuvant chemotherapy and initiating immunotherapy. This case highlights the diagnostic and therapeutic challenges of managing SCCOHT during pregnancy and the complex balance of maternal and fetal outcomes. Early diagnosis, coordinated multidisciplinary care, and timely intervention are critical, although the prognosis remains poor despite aggressive multimodal treatment.